(untitled) (Fiep Bulletin - online, 2013)
The indiscriminate use of sweeteners and extrapolation of its Acceptable Daily Intake (ADI) can cause adverse health effects. This study aimed to verify the sweeteners declared on labels in beverages with added sweeteners sold in hypermarkets of Natal-RN, comparing the amounts declared with the Brazilian legislation. In addition, the maximum consumption of each beverage for people of 30 kg, 50 kg or 70 kg to reach the ADI was estimated. In January 2011, we collected the main soft drinks, teas and juices with added sweeteners in Natal, with 100% of the samples studied, which corresponded to 39 drinks (8 sodas, 10 teas and 21 juices). It was observed that only 2.6% (n=1) of the drinks were not in accordance with the Brazilian legislation in relation to established limits. There was a wide variation in the maximum amount of daily consumption to reach the ADI in the drinks surveyed. We identified a consumption of 0.47 L to 5.0 L for an individual of 30 kg to reach the ADI, 0.79 L to 8.3 L to a person with 50 kg and 1.1 L to 11.7 L for person weighing 70 kg. Sodium cyclamate was the most limiting sweetener (in 51.3% of drinks assessed), followed by sucralose (28.2%) and acesulfame-k (15.4%). We conclude that there is efficiency in the legislation application and that the consumption of sweetened beverages should be done with caution, noting its composition and labeling not to extrapolate the daily consumption.